Analysis of the Roles of Glucose Transporter 1 and Hexokinase 2 in the Metabolism of Glucose by Extrahepatic Bile Duct Cancer Cells. (March 2015) - Yoon, Sun Och; Jeon, Tae Joo; Park, Joon Seong; Ryu, Yong Hoon; Lee, Jae-Hoon; Yoo, Jung Sik; Kim, Jae Keun; Yoon, Dong Sup; Oh, Eun Ji
Abstract : Purpose of the Report: Extrahepatic bile duct (EHD) cancer varies in uptake of FDG. The aim of the present study was to determine the role of glucose transporter (GLUT) 1 and hexokinase (HK) 2 in the glucose metabolism of EHD cancer cells using immunohistochemistry and 18 F-FDG PET/CT. Methods: Twenty-six patients with EHD cancer who underwent baseline PET/CT and surgery were studied. Biopsies were immunohistochemically analyzed using antibodies against GLUT1 and HK2, and the expression was scored from 0 to 4 according to the percentage of stained cells. SUV and tumor-to-liver ratio (T/Lratio ) were obtained from 18 F-FDG PET/CT data. SUV and T/Lratio and GLUT1 and HK2 expression were compared with histological grades and tumor locations (proximal and distal EHD) to correlate glucose metabolism with the expression of GLUT1 and HK2. Results: SUV, T/Lratio, and GLUT1 and HK2 expression did not differ as a function of histological grade and tumor location. GLUT1 and HK2 were expressed in 20 (76.9%) and 22 (84.6%) of 26 tumor biopsies, respectively. The GLUT1 score, SUV, and T/Lratio increased, and the GLUT1 score, but not the HK2 score, correlated significantly with SUV (ρ = 0.648) and T/Lratio (ρ = 0.703). There was no direct correlation between the expression of GLUT1 and that of HK2 (ρ = 0.2046, P = 0.3161). Conclusions: Although GLUT1 and HK2 regulate intracellular accumulation of FDG in many cancers, only GLUT1 expression was correlated with FDG uptake by EHD cancers.